Barriers to household risk management: Evidence from India - Shawn Cole; Xavier Giné; Jeremy Tobacman; Petia Topalova; Robert Townsend; James Vickery (Federal Reserve Bank of New York, 2009)
Financial engineering offers the potential to significantly reduce the consumption fluctuations faced by individuals, households, and firms. Yet much of this potential remains unfulfilled. This paper studies the adoption of an innovative rainfall insurance product designed to compensate low-income Indian farmers in the event of insufficient rainfall during the primary monsoon season. We first document relatively low adoption of this new risk management product: Only 5-10 percent of households purchase the insurance, even though they overwhelmingly cite rainfall variability as their most significant source of risk. We then conduct a series of randomized field experiments to test theories of why product adoption is so low. Insurance purchase is sensitive to price, with an estimated extensive price elasticity of demand ranging between -.66 and -0.88. Credit constraints, identified through the provision of random liquidity shocks, are a key barrier to participation, a result also consistent with household self-reports. Several experiments find that trust plays an important role in the decision to purchase insurance. We find mixed evidence that subtle psychological manipulations affect purchases and no evidence that modest attempts at financial education change households' decisions to participate. Based on our experimental results, we suggest preliminary lessons for improving the design of household risk management contracts.
Keywords: D14; G11; G22; D81; 330; Insurance; economic development; consumer finance; India; liquidity constraints; trust; Landwirtschaftlicher Familienbetrieb; Risikomanagement; Elementarschadenversicherung; Verhaltensökonomik; Indien